First Report of Root-knot Nematode, Meloidogyne enterolobii , on Luffa cylindrica (L.) in Guangxi, China - Li, Fayu; Shan, Bin; Zhang, Xiaoxiao; Zhao, Wei; Pan, Lingling; Wu, Chaorong; Yang, Shanshan (Plant disease, 2024)
Luffa cylindrica (L.), an annual climbing herb of the Cucurbitaceae family, has a long planting history in China and is deeply loved by people due to its nutritional and medicinal value (Partap S, Kumar A et al., 2012). April 2023, symptoms such as plant dwarfism, decreased yield and serious root-knots appeared on L. cylindrica sampled from a commercial production base in Beihai, Guangxi, China (GPS 21°55'79″ N;109°49'61″ E). The investigated area of L. cylindrica was about 1.3 ha, the incidence of root-knot nematode disease was almost 90%. The roots of 20 L. cylindrica were dug up and many root-knots and egg masses were found. Nematodes in samples at different stages were collected by shallow dish method, and morphological identification was caried out. Males were worm-like, annulated, with the anterior part slightly conical. Females were globular to pyriform. The perineal pattern was oval, with the dorsal arch being moderately high to tall. The tail of the second-stage juvenile (J2) was very slender with a sharp tip. The transparent tail end was clearly visible. Morphological measurements of females (n = 20): body length = 677.2 ± 34.4 μm, body width = 512.8 ± 45.4 μm, stylet = 13.7 ± 0.5 μm, dorsal pharyngeal gland orifice to stylet base (DGO) = 5.7 ± 0.8 μm. The measurements of J2s (n = 20): body length = 412.5 ± 19.4 μm, body wide = 16.2 ± 1.3 μm, stylet lengths = 12.6 ± 0.92 μm, DGO length = 3.1 ± 0.3 μm. Average tail length = 45.44 ± 4.1μm. The observed typical characteristics of M. enterolobii were consistent with those previously described by Yang & Eisenback (1983) and EPPO (2016). J2s hatched by single egg mass were used for DNA extraction and identification of molecular biology. Me-F/Me-R (AACTTTTGTGAAAGTGCCGCTG/TCAGTTCAGGCAGGATCAACC), the specific primers of M. enterolobii, was used to validate this pathogen (Long et al., 2006). Consistent with that described before, the target amplification product was about 236 bp, and no product was obtained from the negative control, M. incognita and M. javanica (Chen et al., 2023). Using V5367/26S (TTGATTACGTCCCTGCCCTTT/TTTCACTCGCCGTTACTAAGG), the rDNA ITS region was obtained and sequenced (Vrain et al., 1992). The target product was 765 bp (GenBank accession no. PQ205316), which was 100% homologous to those M. enterolobii ITS sequence available in the GenBank (KX823372, KJ146863). Koch's postulates were used to verify the pathogenicity of M. enterolobii on L. cylindrica, twelve 2-week-old L. cylindrica were planted in sterilized soil and inoculated with M. enterolobii J2s at a rate of 3,000 individuals per plant. The plants were grown at 26°C in a greenhouse, with non-inoculated controls set up. After 8 weeks, the roots of the non-inoculated plants (n = 12) showed no root-knot and grew well, while all inoculated plants developed root-knots and exhibited stunted growth. The average reproduction factor of the inoculated plants was 19.5, and the average root-knot rating was 7.2 (on a scale of 0 to 10) (Bridge and Page 1980), confirming the pathogenicity of M. enterolobii on L. cylindrica. We found that this is consistent with the description of M. enterolobii infecting Coriandrum sativum in Shanxi, China (Pan et al., 2024) and the infection of Selenicereus costaricensis in Guangxi, China by M. enterolobii (Wu et al., 2023). To our knowledge, this is the first report of M. enterolobii parasitizing L. cylindrica in Guangxi, China. With the increase of vegetable planting area, root-knot nematodes are becoming more and more serious and have become a limiting factor on vegetable production. This finding is of significant importance for vegetable growers to control M. enterolobii in this region, based on which suitable management measures will be taken.